Pengaruh Pembelajaran Etnomatematika Berbasis Android pada Konteks Budaya Pamama terhadap Literasi Numerasi Siswa SMA - Yulius Keremata Lede; Timotius Woda Napu; Mardiyanto Ginto Bili; Olviana Dapa (Media Pendidikan Matematika, 2026)
This study aimed to determine the effect of Android-based ethnomathematics learning using the EBS-PBM Apps application in the context of Pamama culture on improving the numeracy literacy of senior high school students. This study used a quasi-experimental method with a pretest-posttest control group design. The research was conducted in three senior high schools in Southwest Sumba Regency representing three cultural groups, namely Wewewa, Loura, and Kodi. The sample consisted of 132 students divided into experimental and control classes. The research instrument was a pre-test and post-test sheet used to measure students’ numeracy literacy. Data were analyzed using normality test, homogeneity test, paired sample t-test, and F-test. The results showed that all data were normally distributed and homogeneous, with the homogeneity significance value based on mean of 0.399 > 0.05. The paired sample t-test showed a significance value of less than 0.001 < 0.05 with a mean paired difference of -23.818 and t-count of -10.333, indicating a significant increase between pre-test and post-test scores. The F-test result showed that the F-count value was 1.501553886 and the F-table was 1.334382865, indicating significant differences between the experimental and control classes. Thus, Android-based ethnomathematics learning using the EBS-PBM Apps application in the context of Pamama culture significantly improved students’ numeracy literacy.